Shared molecular genetic mechanisms underlie endometriosis and migraine comorbidity - Adewuyi, Emmanuel; Sapkota, Y.; Auta, A.; Yoshihara, K.; Nyegaard, M.; Griffiths, L.R.; Montgomery, G.W.; Chasman, D.I.; Nyholt, D.R. (2020)
Observational epidemiological studies indicate that endometriosis and migraine co‐-occur within individuals more than expected by chance. However, the aetiology and biological mechanisms underlying their comorbidity remain unknown. Here we examined the relationship between endometriosis and migraine using genome‐-wide association study (GWAS) data. Single nucleotide polymorphism (SNP) effect concordance analysis found a significant concordance of SNP risk effects across endometriosis and migraine GWAS. Linkage disequilibrium score regression analysis found a positive and highly significant genetic correlation (rG = 0.38, P = 2.30 × 10−25) between endometriosis and migraine. A meta‐-analysis of endometriosis and migraine GWAS data did not reveal novel genome‐-wide significant SNPs, and Mendelian randomisation analysis found no evidence for a causal relationship between the two traits. However, gene‐-based analyses identified two novel loci for migraine. Also, we found significant enrichment of genes nominally associated (Pgene < 0.05) with both traits (Pbinomial‐-test = 9.83 × 10−6). Combining gene‐-based p‐-values across endometriosis and migraine, three genes, two (TRIM32 and SLC35G6) of which are at novel loci, were genome‐-wide significant. Genes having Pgene < 0.1 for both endometriosis and migraine (Pbinomial‐-test = 1.85 ×10−°3) were significantly enriched for biological pathways, including interleukin‐-1 receptor binding, focal adhesion‐-PI3K‐-Akt‐-mTOR‐-signaling, MAPK and TNF‐-α signalling. Our findings further confirm the comorbidity of endometriosis and migraine and indicate a non‐-causal relationship between the two traits, with shared genetically‐-controlled biological mechanisms underlying the co‐-occurrence of the two disorders.